The Sex Gratification Polemic in the Scope of State Officials viewed from the Normative Perspective of Criminal Law - Lestari, Alika Ayu; Hadi, Dejan Abdul (Law Research Review Quarterly, 2019)
Corruption is like a crime that calculative carried out by them who as educated and cultured communities. One of the dynamisation, in its development motive, is gratification. Inspired of that definition, there are so many substances of the meaning or interpretation that expanding the new acts that can be called as gratification acts. One of the new phenomenon case of gratification is sexual gratification, this case regarded as controversial case because there’s no specific law that can be charged this case. In the Article 12B Law Number 31 in 1999 juncto Law Number 20 in 2001 about Corruption, gratification that means giving extra fee, gift in form of money, goods, discount, loan commision without any interest, trip ticket, housing facility, tour trip, free medication, and other facilities. The other substance meanings that implied are multiple interpretation meanings which have no clear elements on it. Shortly, according to the writers, sexual gratification motive hasn’t been specifically regulated yet in the law that causes many officials do a corruption by receiving or giving a sexual gratification which is separated from the elements of gratification as the corruption, so that, it’s needed specific formulation about sexual gratification in the Corrupytion Law with more strict sanction against the perpetrator of sexual gratification, because his act already harm the dignity nation and the dignity of this country by immoral deed and needed the social sanction for the perpetrator.